2007
DOI: 10.1007/s10637-007-9042-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ABT-751 against childhood cancer models in vivo

Abstract: ABT-751 demonstrated intermediate activity against this tumor panel. Neuroblastoma models appear somewhat more sensitive to this agent, with objective regressions also in rhabdomyosarcoma and Wilms tumor. ABT-751 was also active in several tumor lines intrinsically refractory to vincristine or paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…These are human Wilms tumors propagated subcutaneously in SCID (severe combined immunodeficiency) mice that have been successfully used as a model for sporadic Wilms tumor (41,42). These tumors were removed from the mice, dissociated, separated from host cells, and loaded with Fura-2 to measure changes in cytosolic Ca 2ϩ concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are human Wilms tumors propagated subcutaneously in SCID (severe combined immunodeficiency) mice that have been successfully used as a model for sporadic Wilms tumor (41,42). These tumors were removed from the mice, dissociated, separated from host cells, and loaded with Fura-2 to measure changes in cytosolic Ca 2ϩ concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Ca 2ϩ measurements were made using a Leica DMI 6000B fluorescence microscope controlled by Slidebook software (Intelligent Imaging Innovations, Denver, CO). Fluorescence emission at 505 nm was monitored while alternating between 340-and 380-nm excitation wavelengths at a frequency of 0.67 Hz; intracellular Ca 2ϩ measurements are shown as 340/380 nm ratios obtained from groups (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) of single cells.…”
Section: Methodsmentioning
confidence: 99%
“…81 Pre-clinical studies of this agent found it to be most effective in neuroblastoma models and a phase I study showed it to be safe. 82,83 The results of a recently concluded phase II trial of ABT-751 in children with relapsed or refractory neuroblastoma are pending publication.…”
Section: New Treatment Strategiesmentioning
confidence: 99%
“…ABT-751 is a novel oral anti-mitotic agent that binds to the colchicine binding site rather than the vincristine binding site on b-tubulin, and inhibits polymerization of microtubules. Importantly, ABT-751 is active against tumor models that are otherwise resistant to vincristine and doxorubicin [Morton et al, 2007]. A COG Phase II study of this compound is currently underway, based on Phase I results showing an encouraging median time-to-progression of 16 weeks in 35 children with relapsed neuroblastoma [Fox et al, 2008].…”
Section: Antimitoticsmentioning
confidence: 99%